2023
DOI: 10.1038/s41467-023-42582-y
|View full text |Cite
|
Sign up to set email alerts
|

A carbon-nitrogen negative feedback loop underlies the repeated evolution of cnidarian–Symbiodiniaceae symbioses

Guoxin Cui,
Jianing Mi,
Alessandro Moret
et al.

Abstract: Symbiotic associations with Symbiodiniaceae have evolved independently across a diverse range of cnidarian taxa including reef-building corals, sea anemones, and jellyfish, yet the molecular mechanisms underlying their regulation and repeated evolution are still elusive. Here, we show that despite their independent evolution, cnidarian hosts use the same carbon-nitrogen negative feedback loop to control symbiont proliferation. Symbiont-derived photosynthates are used to assimilate nitrogenous waste via glutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…The authors proposed that increased coral host central carbon metabolism generates metabolites required for ammonium assimilation, leading to increased ammonium assimilation by the host and less available to the symbiont. Reduced ammonium availability for the symbiont limits growth and symbiont photosynthesis [21]. [22] provided evidence that translocation of photosynthates stimulates ammonium assimilation in the host, reducing nitrogen availability and consequently, symbiont population growth rate declines this would allow for greater translocation of excess carbon relative to the population growth rate [10,28,29,119].…”
Section: B Symbiotic Coral Larvae Utilize Nitrogen Assimilation and S...mentioning
confidence: 99%
See 4 more Smart Citations
“…The authors proposed that increased coral host central carbon metabolism generates metabolites required for ammonium assimilation, leading to increased ammonium assimilation by the host and less available to the symbiont. Reduced ammonium availability for the symbiont limits growth and symbiont photosynthesis [21]. [22] provided evidence that translocation of photosynthates stimulates ammonium assimilation in the host, reducing nitrogen availability and consequently, symbiont population growth rate declines this would allow for greater translocation of excess carbon relative to the population growth rate [10,28,29,119].…”
Section: B Symbiotic Coral Larvae Utilize Nitrogen Assimilation and S...mentioning
confidence: 99%
“…The mechanisms underlying the onset and progression of coral bleaching are complex and a topic of intense scientific study (see a recent review in [19]). Research in the last two decades has demonstrated that oxidative stress [19,20], as well as carbon and nitrogen imbalance can drive dysbiosis and lead to bleaching [19,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations